Mental health and substance use among elite para-athletes: An cross-sectional survey - Tiffany Hartmann; Nikolai Kiselev; Malte Claussen; Christian Imboden; Olivia Stoffel; Andreas Heiniger; Ceren Acarturk; Christoph Kreinbucher-Bekerle; Michael Schaub (Bern Open Publishing, 2024)
Objective The scientific studies on the mental health and substance use among elite para-athletes are rare (Lardi et al., in preparation; Lüdi et al., 2023). However, the shows similarities as well as differences to the regular elite athletes' populations (Rice et al., 2016; Swartz et al., 2019). The aim of this study was to investigate the mental health and substance use of para-athletes (PAs) from their perspective, in order to gain an overview of the situation in elite para-sport and to potentially create a basis for prevention campaigns and, if necessary, interventions. Methodology An online survey (SoSciSurvey) was used to create a questionnaire, which was translated into eight languages to reach PAs internationally. In addition to socio-demographic and sports-specific (Para-Sport, PS) variables, psychological and physical factors, as well as substance use, were assessed using standardized instruments. Results (CAVE: at the time at submission preliminary since the survey ends by the end of November/The final results will be presented at the congress): The PAs (N = 82) showed different prevalences regarding mental disorders compared to data from the general population and regular elite athletes, with disorder-specific deviations. There were significant gender differences in psychological distress (K-10, p < .001), depression severity (PHQ-9, p < .001), and anxiety severity (GAD-7, p < .001). The majority of PAs reported good or very good mental (69.51%) and physical (64.63%) health, and these results significantly correlated (p < .001) with a strong effect size. PAs were more likely to disclose and seek support in professional than in private settings. 51.22% of the PAs felt disadvantaged in everyday life, and in PS, it was 29.27%. The BA and K-10 did not correlate significantly (p > .05), but there was a significant correlation (p < .001) between discrimination in PS and the K-10. The results of discrimination in everyday life and in PS both significantly correlated with the WHODAS-12 (p < .01, and p < .001), with a weak and moderate effect size, respectively. Regarding substance use, 41.46% of PAs reported alcohol, 7.32% nicotine, and 8.54% cannabis use. The AUDIT-C did not significantly correlate with the K-10 or the WHODAS-12 (p > .05), and there was no significant gender difference (AUDIT-C, p > .05). Conclusions Based on the results, prevention should occur in the disorder-specific area and refer to the professional services, social support, focusing more on discrimination, and include substance use (alcohol and cannabis). It is important to consider that PAs are a vulnerable population and research gaps still exist. References Lardi, M., Kiselev, N., Imboden, C., Stoffel, O., Heiniger, A., & Schaub, M. (in preparation). Unveiling the shadows - Substance use among para-athletes: A qualitative study with Swiss elite para-athletes. Lüdi, L., Pfarrwaller, G., Imboden, C., Stoffel, O., Schlüssel, M., Heiniger, A., Kleim, B., & Kiselev, N. (2023). Perspectives on mental health and well-being: Voices of Swiss paralympic athletes. Sports Psychiatry: Journal of Sports and Exercise Psychiatry. Advance online publication. https://doi.org/10.1024/2674-0052/a000057 Rice, S. M., Purcell, R., De Silva, S., Mawren, D., McGorry, P. D., & Parker, A. G. (2016). The mental health of elite athletes: A narrative systematic review. Sports Medicine, 46, 1333-1353. https://doi.org/10.1007/s40279-016-0492-2 Swartz, L., Hunt, X., Bantjes, J., Hainline, B., & Reardon, C. L. (2019). Mental health symptoms and disorders in Paralympic athletes: A narrative review. British Journal of Sports Medicine, 53(12), 737-740. https://doi.org/10.1136/bjsports-2019-100731